Nasilne meje, varnostnizacija in kriminalizacija solidarnosti - Zorn, Jelka (Socialno delo, 2021)
Autonomy of social work is undermined by securitization, which is a form of structural violence against migrants and refugees. Police pushbacks at the European borders are violation of international standards and the right to have rights. In such racist social environment, groups and individuals, who show solidarity with migrants, are also criminalised and threatened. Authorities consider solidarity a crime. The author combines research methods of observance participation and auto-ethnography. These are applied to search the position of social work in order not to reproduce inequalities and violence, but on the contrary, to conceptualize and work in line with professional values.
Keywords: activism; aktivizem; autonomy; avtonomija; begunci; migracije; migration; policijsko potiskanje; pushback; refugees; social work; socialno delo